Transesterification of Moringa Oleifera Seed Oil by Sodium Silicate Catalyst Using Different Co-Solvents - K. Moorthi, Puvaniswaran; Shrivastava, Preeti; Krishnan, Soundarajan (International Journal of Engineering and Technology, 2018)
Biodiesel is a renewable energy source which is derived as an alternate fuel for diesel engine. It is produced by transesterification process. Moringa oleifera seed oil has been extracted using n-hexane by solvent extraction method. The high flashpoint of Moringa oleifera oil is a beneficial safety feature so that it can safely be stored at room temperature. The study examines the production of biodiesel using Moringa oleifera seed oil with sodium silicate as catalyst and different co-solvents. The biodiesel produced from Moringa oleifera seed oil exhibits high yield using diethyl-ether as co-solvent with 60oC as the reaction temperature and 1 hour as the reaction time. Furthermore, the optimum ratio of methanol to oil is 7:1 and the amount of catalyst required to produce highest yield is 0.30 g. Moreover, the optimum ratio of methanol to co-solvent is 1:1 ratio. It has been found that the saponification value and free fatty acid are 170.2 mg of KOH/ g of oil and 0.33 %, respectively. The moisture content of biodiesel is 0.04% with higher calorific value when compared to diesel and vegetable oil. The pH and cloud point of biodiesel recorded are 7.37 and 18oC, respectively. All these values have been found to be within the range of American Standard for Testing Material for biodiesel. Only the acid value has fallen outside the ASTM limits. Hence, it can be concluded that biodiesel produced from Moringa oleifera seed oil has the potential to be an alternate fuel and the energy of the future.Â